Effects of adrenergic blocking agents on the actions of thyroid stimulating hormone and dibutyryl-cyclic-3', 5' -A.M.P. on iodide transport - Pansegrouw, D. F (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1970.